Modelamiento y Simulación de las Etapas de Modulación Digital y Acceso al Medio para un Satélite de Órbita Baja - Gaona García, Elvis Eduardo; Rodríguez Garay, Juanita; Florez Contreras, Camilo Humberto (Ingeniería, 2007)
This paper describes the modulation scheme and channel access for a satellital system of low orbit based on GFSK and FHSS/TDMA. Through simulations these scheme are compared with systems used conventionally in the working of satellites LEO. This as a result of the grade project developed in the Groupof Investigation GITUD.